Multiple minute digitate hyperkeratosis - a peculiar entity - Inês Coutinho; Ana Rita Gameiro; Miguel Pinto Gouveia; José Carlos Cardoso; Américo Figueiredo (Sociedade Brasileira de Dermatologia, 2015)
Abstract Multiple minute digitate hyperkeratosis is a rare, non-follicular dermatosis, with fewer than 30 cases described worldwide. It can be either acquired or inherited in an autosomal dominant pattern. We describe the case of an 83-year old patient with life-long, multiple, digitate, milimetric lesions, and a positive family history for the same dermatosis.